2021
DOI: 10.1177/13623613211065797
|View full text |Cite
|
Sign up to set email alerts
|

Using evaluative frameworks to examine the implementation outcomes of a cognitive behavioral therapy program for autistic students with anxiety within public school settings

Abstract: Cognitive behavioral therapy for youth with autism spectrum disorder and anxiety is effective, but disparities exist in accessing these programs. Training school providers to deliver cognitive behavioral therapy may help to address these disparities. However, little is known about how cognitive behavioral therapy programs are implemented by interdisciplinary school providers and the broader impact of these programs. This study aimed to address this gap and was part of a larger trial that examined the effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Particularly within the studied population of autistic students, interactions serve as a common coping strategy for symptoms of comorbid mental health conditions. Concerning the practicality of an emotion-responsive assessment, as indicated by the NEGP, disparate results were noted (27). This comparison highlights that although the combined NEGP and SSRS assessment effectively predicted both autism outcomes with significant effect sizes, the integration of NEGP items did not enhance treatment accuracy for either outcome and even led to a decrease in Emotional force value.…”
Section: Effectiveness Of the Ssrs In Evaluating Emotion-related Trea...mentioning
confidence: 86%
“…Particularly within the studied population of autistic students, interactions serve as a common coping strategy for symptoms of comorbid mental health conditions. Concerning the practicality of an emotion-responsive assessment, as indicated by the NEGP, disparate results were noted (27). This comparison highlights that although the combined NEGP and SSRS assessment effectively predicted both autism outcomes with significant effect sizes, the integration of NEGP items did not enhance treatment accuracy for either outcome and even led to a decrease in Emotional force value.…”
Section: Effectiveness Of the Ssrs In Evaluating Emotion-related Trea...mentioning
confidence: 86%
“…An additional direction would be to explore the optimal dosage for delivery of FYF-SB. Although exit interviews from the pilot study indicated that the 40-min 12 weekly sessions were recommended (Pickard et al, 2021), future research could investigate the differential impact of varied intervention dosage on treatment outcome. Examining the relationship between program dosage, adherence and facilitator competence on child outcome will be important.…”
Section: Future Directionsmentioning
confidence: 99%
“…That is, although both interventions are rooted in CBT principles, ZOR primarily uses psychoeducation and direct teaching of coping strategies to improve selfregulation, while FYF-SB pairs psychoeducation with graded exposure in which students practice facing their fears a little bit at a time to reduce anxiety symptoms. Although graded exposure plays a critical role in anxiety outcomes and is considered a core component of CBT [33,34], previous research has demonstrated that graded exposure is often a novel treatment strategy for school-based providers that may be logistically complicated to implement within schools [35]. Thus, in addition to their distinct intervention targets, comparing ZOR and FYF-SB may provide insight into the feasibility of each intervention's core components when implemented within school settings.…”
Section: Introductionmentioning
confidence: 99%